PEMBELAJARAN KEWIRAUSAHAAN BERBASIS PENGALAMAN PADA PROGRAM STUDI MANAJEMEN UNIVERSITAS NUSANTARA PGRI KEDIRI - Sardanto, Rino (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
The aim of the research is to describe the implication of entrepreneurial learning based on the experience in Management program study. This research uses qualitative approach. Data collection techniques used observation, interview and documentation. The data were analyzed using reduction, data presenting and conclusion. The result of the research shows that the experiential learning makes the students have their own experience based on knowledge, what is seen, heard and felt. Intrapersonal ability such as cultivate self-confidence, ability to overcome problems, independence and responsible and critical thinking increases